2015
DOI: 10.1371/journal.pone.0116936
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Function during Acute High-Altitude Exposure in a Large Group of Healthy Young Chinese Men

Abstract: ObjectiveThe purpose of this study was to observe left ventricular function during acute high-altitude exposure in a large group of healthy young males.MethodsA prospective trial was conducted in Szechwan and Tibet from June to August, 2012. By Doppler echocardiography, left ventricular function was examined in 139 healthy young Chinese men at sea level; within 24 hours after arrival in Lhasa, Tibet, at 3700 m; and on day 7 following an ascent to Yangbajing at 4400 m after 7 days of acclimatization at 3700 m. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…The systolic LVEF was slightly but significantly reduced at 2,590 m -albeit with a median decrease of only 5%, which should be interpreted with caution, since it could be within the range of measurement variability [33]. In contrast, recent studies have reported an increase in EF with acute exposure to 3,700 m [34] (n = 139) and 3,750 m (n = 15) in healthy subjects [28]. Thus, the measured reduction in EF in our COPD collective seems to be noteworthy.…”
Section: Discussionmentioning
confidence: 67%
“…The systolic LVEF was slightly but significantly reduced at 2,590 m -albeit with a median decrease of only 5%, which should be interpreted with caution, since it could be within the range of measurement variability [33]. In contrast, recent studies have reported an increase in EF with acute exposure to 3,700 m [34] (n = 139) and 3,750 m (n = 15) in healthy subjects [28]. Thus, the measured reduction in EF in our COPD collective seems to be noteworthy.…”
Section: Discussionmentioning
confidence: 67%
“…Myocardial performance index has been used to investigate different populations, such as patients with heart failure [2], acute myocardial infarction [3], heart transplants [4], COPD [25], patients with chronic ischemic cardiomyopathy who have undergone revascularization [26], as well as in healthy young men during high altitude exposure [27]. MPI has also been investigated in relation to age [28].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxic conditions as during high‐altitude exposure challenge LVdiastole by decreasing cardiac energy supply, increasing sympathetic nervous activity and pulmonary hypertension . Impaired diastolic function and its main hemodynamic consequence, that is, an increased LV end‐diastolic pressure (LVEDP), are of clinical importance at high altitude because a recently hypothesized deterioration might increase pulmonary capillary pressure and thereby increase the risk for high‐altitude pulmonary edema (HAPE) . Furthermore, impaired diastolic function might contribute to the reduction in stroke volume (SV) at high altitude .…”
Section: Introductionmentioning
confidence: 99%